Flexor carpi radialis muscle atrophy due to cervical spondylotic amyotrophy - Fatma Elleuch; Wafa Elleuch; Sameh Ghroubi; Mohamed Habib Elleuch (Clinical Case Reports, 2024)
Key Clinical Message Presenting a rare case of flexor carpi radialis atrophy secondary to cervical spondylotic amyotrophy. Abstract A 52‐year‐old man with a history of cervicobrachial neuralgia presented with an advanced atrophy of the right flexor carpi radialis muscle with a groove hollowed out on the anterior surface of the right forearm. The spine MRI showed that this rare atrophy was related to a cervical spondylotic amyotrophy.